Prinsip Etis, Logis, dan Estetis dalam Proses Penciptaan Tari Kreasi Baru Sangita Praja - Wisnu Dermawan; Y. Adityanto Aji; Otok Fitrianto (Journal of Mandalika Social Science, 2025)
Dance creation is an artistic practice that extends beyond aesthetic achievement by incorporating ethical and logical considerations into every creative decision. However, studies integrating these three dimensions within a unified conceptual framework remain limited, particularly in the context of Indonesian dance creation. This study aims to examine the application of ethical, logical, and aesthetic principles in the creative process of the dance work Sangita Praja and to formulate a conceptual model explaining the relationships among these principles. A qualitative approach employing narrative inquiry was adopted. Data were collected through in-depth interviews, participant observation, documentation of the creative process, and the choreographer's reflective notes. The data were analyzed using thematic analysis by integrating participants' narratives with interpretations grounded in choreography theory and practice-based artistic research. The findings reveal that the creation of Sangita Praja evolved through a dynamic interaction among ethical, logical, and aesthetic principles that continuously influenced one another throughout the creative process. Ethical principles guided value orientation and artistic responsibility, logical principles structured the choreography coherently, while aesthetic principles shaped expressive quality and artistic experience. Based on these findings, this study proposes the Ethical–Logical–Aesthetic Choreographic Framework (ELA Framework) as a conceptual model that explains the integration of these three principles within choreographic practice. The proposed framework contributes to the development of Practice-Based Research and choreography studies by positioning dance creation as a reflective practice that simultaneously produces artistic works and scholarly knowledge.